(untitled) (Revista de Crítica Literaria Latinoamericana, 2014)
Claudia Llosa’s film The Milk of Sorrow received a high level of media exposure as a result of the many prizes it won in important film festivals, as well as its nomination for the Best Foreign Language Film Academy Award in 2009. In this article I analyze this film’s insertion into the global market of images of Peru. Discussing the film’s representation of choledad as well as the way the Peruvian president at the time, the dwellers of the Manchay district, and others made use of the film’s success for their own purposes, I propose that an aesthetic exoticism inscribes the integration of rural migrants to Lima within a utopian narrative of consumerist success that attempts to conceal the tension between remembering and forgettting the violence and pain of the recent past.